2022
DOI: 10.1002/adfm.202112225
|View full text |Cite
|
Sign up to set email alerts
|

Insoluble Naphthoquinone‐Derived Molecular Cathode for High‐Performance Lithium Organic Battery

Abstract: Organic electrode materials have attracted significant attention for rechargeable lithium organic batteries owing to the anticipated electrochemical property and environmentally friendly features. Benzoquinone and naphthoquinone as the simplest quinone substances have been considered as promising cathode materials because of their high theoretical specific capacities and discharge voltages. However, they are soluble in most organic liquid electrolytes, which results in poor electrochemical performance. Herein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Zhao et al prepared three naphthoquinone-derived materials using naphthoquinone (NQ) with 1,2-, 1,3-, and 1,4-benzenedithiols. 170 The obtained 2,2′-(1,4-phenylenedithio) bis(1,4-naphthoquinone) (1,4-PNQ) shows the best electrochemical performance owing to the lowest solubility caused by the strong intermolecular 105 48.2 ∼2.5 ∼690 (50 mA g −1 ) ∼72%, 20 cycles TSP 106 76 1 ∼610 (1 C) ∼54%, 600 cycles SAC-350 107 42.1 2.5−3.0 ∼810 (2 C) 80%, 1000 cycles SC@A 108 47. 92%, 400 cycles SPAN 120 35.2 5.7 520 (2nd, 0.2 mA cm −2 ) 92%, 240 cycles SPAN 123 / 0.85 ∼1310 (2nd, 0.4 C) 76.3%, 1000 cycles S@pPAN 124 37.64 2.5 1729 (2nd, 200 mA g −1 ) 98.4%, 100 cycles SPAN 125 39.8 1.5 ∼620 (2nd, 0.…”
Section: Covalent-based Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al prepared three naphthoquinone-derived materials using naphthoquinone (NQ) with 1,2-, 1,3-, and 1,4-benzenedithiols. 170 The obtained 2,2′-(1,4-phenylenedithio) bis(1,4-naphthoquinone) (1,4-PNQ) shows the best electrochemical performance owing to the lowest solubility caused by the strong intermolecular 105 48.2 ∼2.5 ∼690 (50 mA g −1 ) ∼72%, 20 cycles TSP 106 76 1 ∼610 (1 C) ∼54%, 600 cycles SAC-350 107 42.1 2.5−3.0 ∼810 (2 C) 80%, 1000 cycles SC@A 108 47. 92%, 400 cycles SPAN 120 35.2 5.7 520 (2nd, 0.2 mA cm −2 ) 92%, 240 cycles SPAN 123 / 0.85 ∼1310 (2nd, 0.4 C) 76.3%, 1000 cycles S@pPAN 124 37.64 2.5 1729 (2nd, 200 mA g −1 ) 98.4%, 100 cycles SPAN 125 39.8 1.5 ∼620 (2nd, 0.…”
Section: Covalent-based Polymersmentioning
confidence: 99%
“…The development of quinone-based organosulfur copolymers can be divided into two categories. One is that the sulfur atoms are not used as redox sites for the energy storage, while the sulfur-containing components only serve as bridging agents to reduce the solubility of quinone-based compounds in the electrolyte via polymerization. The other one is that both quinone and sulfides, i.e., polysulfides containing S–S bonds, act as redox active sites contributing capacities. In addition, the fast reaction kinetics of quinones can facilitate the conversion of polysulfides. …”
Section: Organosulfur As Cathode Materials In Lithium Batteriesmentioning
confidence: 99%
“…The newly emerging peak centered at 1651 cm −1 can be assigned to the vibration of CO bonds in the dehydrated C 6 O 6 sample. [17][18][19] Note that the FT-IR spectrum of the C 6 O 6 electrode matches well with C 6 O 6 powder, confirming that there is little chemical interaction between super P carbon/PVDF binder and C 6 O 6 during the electrode preparation.…”
Section: Physicochemical Properties Of C 6 O 6 and Its Derived Electrodementioning
confidence: 87%
“…S3a. † For BFBOMe, the C-O-C stretching vibration peaks can be observed at 1216 cm À1 and 1025 cm À1 , indicating the existence of the methoxy group on phenyl rings, 22 while the two characteristic peaks of C-O-C completely disappeared in QFQ. Moreover, the C]O vibration peak can be clearly observed at 1619 cm À1 in QFQ, which strongly suggested that all of the methoxy groups in the intermediate have been successfully oxidized to carbonyl.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Expanding the p-conjugation system through C]C, C^C, C-S-C or aryl rings such as benzene, anthraquinone, naphthalene or polycyclic aromatic hydrocarbons. [17][18][19][20][21][22] Among the above strategies, expanding p-conjugation was the most widely studied because the structure modication was the most easily realized, whereas the additional p-linker also increases molecular weight, but generally cannot provide active sites and thus tends to result in decreased specic capacity. Therefore, a balance needs to be pursued between the high specic capacity and the expanded molecular conjugation to avoid dissolution in electrolytes.…”
Section: Introductionmentioning
confidence: 99%